Linking Hybrid Strategy to Firm Performance: Exploring the Mediating Role of Innovation - Thapa, Bala Ram; Chalise, Mahananda (Nepal Journal of Multidisciplinary Research, 2025)
Background: In the current competitive environment, companies are increasingly implementing hybrid strategies that merge cost leadership and differentiation. Nonetheless, the success of these strategies in enhancing company performance remains a matter of debate, especially in emerging markets. Objective: This study explores the impact of hybrid strategies on firm performance in Nepal’s commercial banking sector, focusing on the mediating role of innovation. Methods: Data collected from 108 executives across 14 commercial banks were analyzed using Smart PLS-SEM. Findings: The hybrid approach did not have a direct impact on company performance; rather, it significantly affected innovation, which subsequently had a positive effect on performance. This suggests that innovation completely mediates the relationship between strategy and firm performance. Conclusion: Innovation is essential for translating the hybrid strategy into improved performance. Implications: Managers must ensure that innovation aligns with strategy, while policymakers should foster innovation ecosystems within the banking industry.